2012
DOI: 10.1016/j.jaci.2012.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Human versus mouse eosinophils: “That which we call an eosinophil, by any other name would stain as red”

Abstract: The respective life histories of humans and mice are well defined and describe a unique story of evolutionary conservation extending from sequence identity within the genome to the underpinnings of biochemical, cellular, and physiological pathways. As a consequence, the hematopoietic lineages of both species are invariantly maintained, each with identifiable eosinophils. This canonical presence nonetheless does not preclude disparities between human and mouse eosinophils and/or their effector functions. Indeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
163
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 169 publications
(166 citation statements)
references
References 150 publications
2
163
0
1
Order By: Relevance
“…The presence of such a nucleus in mouse eosinophils is considered a sign of cell immaturity (66,67), suggesting that pulmonary rEos retain an immature phenotype when spreading into the lungs. Using histochemistry, we further showed that lung rEos were located in the parenchyma, which contrasts with the localization of eosinophils in asthma, in which eosinophils are classically thought to infiltrate the peribronchial area (68).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such a nucleus in mouse eosinophils is considered a sign of cell immaturity (66,67), suggesting that pulmonary rEos retain an immature phenotype when spreading into the lungs. Using histochemistry, we further showed that lung rEos were located in the parenchyma, which contrasts with the localization of eosinophils in asthma, in which eosinophils are classically thought to infiltrate the peribronchial area (68).…”
Section: Discussionmentioning
confidence: 99%
“…We recognize that the use of Th2-polarized chronic inflammatory mice that are specifically engineered to understand the shortterm/long-term consequences of pulmonary eosinophil activities is limited as a model of lung dysfunction characteristic of human respiratory disease. Instead, our goal was a reductionist approach to understanding mechanisms potentially mediating eosinophil activities during Th2-driven inflammatory events, which we have suggested are likely shared between humans and mice (28). Thus, if further studies suggest that our observations in mice are translatable to patients with asthma, this result would have significant implications by suggesting that the chronic presence of eosinophils in the lungs of some patients with asthma may elicit sustained expression of pulmonary cys-leukotrienes and, in turn, progressive lung fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Post-hoc analysis of differences and comparison of differences between pairs of data were performed with the Wilcoxon rank test and the Mann-Whitney U test for paired and unpaired observations, respectively. Figure 2B) (13,14). Romanowsky staining of flow cytometrically sorted cells demonstrated an intense eosinophilic cytoplasmic staining, with a characteristic eosinophil-defining ring-shaped nucleus ( Figure 2C).…”
Section: Tolerance Is Associated With An Influx Of Recipient-derived mentioning
confidence: 97%